(untitled) (Indonesian Economic Justice Review, 2025)
This paper critically examines Indonesia’s controversial Omnibus Law, which was introduced as a major reform to streamline regulations, improve the business climate, and attract foreign investment. While the law is hailed for its potential to enhance economic growth, it has raised significant concerns regarding labor rights and social equity. This study explores the key provisions of the Omnibus Law, focusing on its impact on labor regulations, job security, and workers’ rights. The paper analyzes how the law’s deregulation of labor markets, particularly its relaxation of rules on minimum wages, severance pay, and outsourcing, affects income inequality and job quality, particularly for vulnerable workers in low-wage sectors. Furthermore, the study investigates how the law’s broader economic objectives—such as promoting foreign direct investment—might disproportionately benefit multinational corporations and wealthy elites, while exacerbating existing social and economic disparities. By examining both the legal provisions and the socio-economic outcomes of the Omnibus Law, the paper argues that while it may stimulate economic growth, it risks undermining social equity and labor justice. The paper concludes by suggesting policy reforms that balance economic development with the protection of workers’ rights and the promotion of inclusive growth.